2015
DOI: 10.1002/joc.4414
|View full text |Cite
|
Sign up to set email alerts
|

Why is the Bay of Bengal experiencing a reduced rate of sea surface warming?

Abstract: ABSTRACT:The sea surface temperature (SST) in the Bay of Bengal (BoB) during the period 1960-1995 showed a decadal cycle, riding over a warming trend. The disruption of the decadal cycle was noticed post-1995 and was followed by a slowdown in the sea surface warming. The cause for the disruption of the SST decadal cycle was the weakening of the link between SST and sunspot number. The rising trend in the SST is due to the increasing atmospheric CO 2 concentration. The post-1995 SST slowdown was due to the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…Studies found that the entire Indian Ocean has been warming over the past half-century (Chambers et al ., 1999; Alory et al ., 2007; Du & Xie, 2008; Rao et al ., 2012; Dong et al ., 2014). A significant increase of water temperature in the BoB, as noted in this study, is supported by the findings of D'Mello & Prasanna Kumar (2016), who claimed an increase in SST at a rate of 0.014°C per year over the period of 1960–2011. Adding to that, the sunspot cycle was partially controlling the rising trend of temperature in the BoB (White et al ., 1997).…”
Section: Resultssupporting
confidence: 90%
“…Studies found that the entire Indian Ocean has been warming over the past half-century (Chambers et al ., 1999; Alory et al ., 2007; Du & Xie, 2008; Rao et al ., 2012; Dong et al ., 2014). A significant increase of water temperature in the BoB, as noted in this study, is supported by the findings of D'Mello & Prasanna Kumar (2016), who claimed an increase in SST at a rate of 0.014°C per year over the period of 1960–2011. Adding to that, the sunspot cycle was partially controlling the rising trend of temperature in the BoB (White et al ., 1997).…”
Section: Resultssupporting
confidence: 90%
“…Such a link between the decadal cycle and SST is also seen in the eastern part of the North Indian Ocean, i.e. the Bay of Bengal, from 1960 to 1995 (D'Mello and Prasanna Kumar, ). However, this decadal relation between AS SST and sunspot number cycle is disrupted post‐1995, as can be seen in Figure .…”
Section: Resultsmentioning
confidence: 90%